Vloga proteomike v bolniku prilagojeni laboratorijski medicini - Božič, Borut (Laboratorijska medicina, 2022)
Over the past years, the technology of mass spectrometry- -based proteomics has dramatically improved. Coupling with high-throughput affinity-based technologies will improve clinical utility of protein biomarkers. However, it is difficult to standardize proteomic approaches and potential of proteomics in translational research and precision medicine is yet to be fully exploited. The fact that proteomics represents a level between the genotype and the phenotype opens some specific ethical dilemmas and challenges for laboratory medicine.
Keywords: biooznačevalci; Etika; Laboratorijska medicina; proteini; Proteomika